2018
DOI: 10.1002/jcsm.12295
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of adjunct testosterone for cancer‐related muscle loss in men and women

Abstract: BackgroundCancer cachexia negatively impacts cancer‐related treatment options, quality of life, morbidity, and mortality, yet no established therapies exist. We investigated the anabolic properties of testosterone to limit the loss of body mass in late stage cancer patients undergoing standard of care cancer treatment.MethodsA randomized, double‐blind, placebo‐controlled phase II clinical trial was undertaken to assess the potential therapeutic role of adjunct testosterone to limit loss of body mass in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 53 publications
4
93
2
2
Order By: Relevance
“…During this time, there has been a change in the consideration of cachexia from a ‘very late change’ and inescapable event to ‘an early phenomenon’ with signs of cachexia present upon primary cancer diagnosis even if weight loss has not yet occurred. This has led to the recent shift in developing effective treatments aimed at preventing rather than reversing the symptoms, as seen in the earlier studies …”
Section: Introductioncontrasting
confidence: 86%
See 1 more Smart Citation
“…During this time, there has been a change in the consideration of cachexia from a ‘very late change’ and inescapable event to ‘an early phenomenon’ with signs of cachexia present upon primary cancer diagnosis even if weight loss has not yet occurred. This has led to the recent shift in developing effective treatments aimed at preventing rather than reversing the symptoms, as seen in the earlier studies …”
Section: Introductioncontrasting
confidence: 86%
“…[4][5][6] Recent publications have shown progress in a number of areas including the ghrelin receptor agonist anamorelin, which possesses both anabolic and appetite-stimulating properties, as per ROMANA 1, 2, and 3 studies, 7,8 the novel non-selective beta-blocker with central 5-HT1a and partial β2 receptor agonist espindolol, which possesses both anabolic and anti-catabolic properties, as per ACT-ONE study, 9 and the anabolic properties of testosterone. 10 During this time, there has been a change in the consideration of cachexia from a 'very late change' and inescapable event to 'an early phenomenon' with signs of cachexia present upon primary cancer diagnosis even if weight loss has not yet occurred. This has led to the recent shift in developing effective treatments aimed at preventing rather than reversing the symptoms, as seen in the earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…Wright et al reported that, in patients with advanced cancer undergoing early-phase standard-of-care therapy, 7 weeks of adjunct testosterone treatment improved lean body mass as well as the quality of life and physical activity. 68 Dieli-Conwright et al recently reported that combined resistance and aerobic exercises significantly attenuated sarcopenic obesity in patients with breast cancer. 69 A phase III clinical trial (NCT02330926) is currently evaluating whether multimodal interventions can improve the outcomes of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wright et al . reported that, in patients with advanced cancer undergoing early‐phase standard‐of‐care therapy, 7 weeks of adjunct testosterone treatment improved lean body mass as well as the quality of life and physical activity . Dieli‐Conwright et al .…”
Section: Discussionmentioning
confidence: 99%
“…66 Therapies that utilize or target ghrelin, 67,68 androgen receptors, 69 interleukin-1α, 70,71 β receptor blockade, 72 testosterone, 73 and myostatin 74 have been evaluated in randomized clinical trials. 66 Therapies that utilize or target ghrelin, 67,68 androgen receptors, 69 interleukin-1α, 70,71 β receptor blockade, 72 testosterone, 73 and myostatin 74 have been evaluated in randomized clinical trials.…”
Section: Pharmacotherapy For Body Composition Managementmentioning
confidence: 99%